Perlindungan Konsumen Terhadap Standar Kehalalan Produk Kosmetika Dan Penggunaannya: Kajian Terhadap Fatwa MUI Nomor 26 Tahun 2013 - Della Agustina; M. Iqbal Irham (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze consumer protection regarding halal standards for cosmetic products based on MUI Fatwa Number 26 of 2013. The research is motivated by the widespread circulation of cosmetics that fail to meet safety and halal standards, resulting in a gap between legal provisions and actual practices in the field. A normative-empirical research method was employed, supported by primary data obtained through interviews with the North Sumatra MUI, BBPOM Medan, and YKI North Sumatra, as well as secondary data comprising relevant laws, regulations, and fatwas. The findings indicate that consumer protection remains suboptimal due to low consumer awareness, limited oversight, and inadequate law enforcement. This situation demonstrates that the objectives of consumer protection have not been fully realized from the perspectives of both positive law and *maqāṣid al-syarī‘ah*. Therefore, synergy among the MUI, BBPOM, YKI, business operators, and the public is essential to achieve more effective consumer protection.